Difference between revisions of "008A Sample Final A, Question 4"
Jump to navigation
Jump to search
(One intermediate revision by the same user not shown) | |||
Line 43: | Line 43: | ||
<td align = "center"><math> x=-1 </math></td> | <td align = "center"><math> x=-1 </math></td> | ||
<td align = "center"><math> x= 0 </math></td> | <td align = "center"><math> x= 0 </math></td> | ||
− | <td align = "center"><math> | + | <td align = "center"><math> x = 2 </math></td> |
<td align = "center"><math> x=5 </math></td> | <td align = "center"><math> x=5 </math></td> | ||
</tr> | </tr> | ||
Line 59: | Line 59: | ||
! Step 3: | ! Step 3: | ||
|- | |- | ||
− | |We take the intervals for which our test point led | + | |We take the intervals for which our test point led the function being negative, (<math>-\infty, -\frac{1}{2}</math>), and (1, 4). |
|- | |- | ||
|Since we we are solving a strict inequality we do not need to change the parenthesis to square brackets, and the final answer is <math>(-\infty, -\frac{1}{2}) \cup (1, 4)</math> | |Since we we are solving a strict inequality we do not need to change the parenthesis to square brackets, and the final answer is <math>(-\infty, -\frac{1}{2}) \cup (1, 4)</math> |
Latest revision as of 20:35, 27 May 2015
Question: Solve. Provide your solution in interval notation.
Foundations: |
---|
1) What are the zeros of the left hand side? |
2) Can the function be both positive and negative between consecutive zeros? |
Answer: |
1) The zeros are , 1, and 4. |
2) No. If the function is positive between 1 and 4 it must be positive for any value of x between 1 and 4. |
Solution:
Step 1: |
---|
The zeros of the left hand side are , 1, and 4 |
Step 2: | ||||||||||
---|---|---|---|---|---|---|---|---|---|---|
The zeros split the real number line into 4 intervals: and . | ||||||||||
We now pick one number from each interval: -1, 0, 2, and 5. We will use these numbers to determine if the left hand side function is positive or negative in each interval. | ||||||||||
x = -1: (-1 -4)(2(-1) + 1)(-1 - 1) = (-5)(-1)(-2) = -10 < 0 | ||||||||||
x = 0: (-4)(1)(-1) = 4 > 0 | ||||||||||
x = 2: (2-4)(2(2) + 1)(2 - 1) = (-2)(5)(1) = -10 < 0 | ||||||||||
x = 5: (5 - 4)(2(5) + 1)(5 - 1) = (1)(11)(4) = 44 > 0 | ||||||||||
Step 3: |
---|
We take the intervals for which our test point led the function being negative, (), and (1, 4). |
Since we we are solving a strict inequality we do not need to change the parenthesis to square brackets, and the final answer is |
Final Answer: |
---|